THE ROLE OF CUSTOMERS’ CULTURAL VALUES IN DEVELOPING E-LOYALTY: EMPIRICAL STUDY ON BSM KUDUS BRANCH - Ningsih, Ekawati Rahayu; Haryono, Tulus; Sawitri, Hunik Sri Runing; Harsono, Mugi (LPPM IAIN Kudus, 2016)
Objective of the study this paper is to discuss result of the study which examines effects of customers’ cultural values in developing e-loyalty in globalization era and integrative model which based on relationship marketing theory. These customers’ cultural values include personal relationship, long-term relationship, credibility among organizations, and English capability. Design/methodology/approach in this study is using triangulation approach consisted of survey on 17 customers, interview with manager, and instrument data processing of 200 respondents based on Structural Equation Modeling (SEM), its result shows that there is significant relation among customers’ cultural values in developing e-loyalty of Sharia banking especially in BSM Kudus Branch. Knowledge provided in this paper is expected to be able to help bank manager in handling issues of decreasing customers’ e-loyalty of Sharia banking by cultural approach.